Cryostimulation improves recovery from oropharyngeal dysphagia after stroke - Zart,Patrícia (2013)
INTRODUCTION: Stroke is considered one of the most frequent neurological causes of oropharyngeal dysphagia. AIM: To determine the effect of cryostimulation on oropharyngeal sensitivity and, subsequently, on the swallowing reaction and premature escape of food in patients with neurogenic dysphagia after stroke. METHODS: Clinical and experimental study. The study enrolled 7 adult subjects, 6 men and 1 woman ranging from 28 to 64 years of age, with a diagnosis of stroke and current oropharyngeal dysphagia without any other underlying disease. The selected subjects underwent speech-language pathology evaluation and videofluoroscopic assessment of the dysphagia. The subjects were then treated with cryostimulation consisting of 10 applications to each structure (anterior faucial pillar, posterior oropharyngeal wall, soft palate, and back tongue) 3 times a day (for a total of 30 daily applications per structure) for 4 consecutive days. The patients were then re-evaluated based on the same criteria. The pre- and post-cryostimulation results of the clinical and videofluoroscopic evaluations were analyzed descriptively and statistically using Student's t-test and Fisher's exact test. RESULTS: Cryostimulation had beneficial effects on oropharyngeal sensitivity in 6 of the 7 subjects. There was also a significant improvement in swallowing and in the premature escape in six subjects. CONCLUSION: Cryostimulation increased sensitivity and subsequently improved the swallowing reaction and premature escape of food in patients with neurogenic dysphagia after stroke. These effects were evident by both speech-language pathology and videofluoroscopic evaluation.